The study of millennial’s attitudes towards the content in Thai digital TV: Case study of Bangkok area - Panapa Chintaradeja (Journal of Green Learning, 2021)
The research aims to study millennial’s attitudes towards the content in Thai digital TV: the case study of Bangkok Area. The samples are 30 Millennial people which are gathered by convenience sampling. The study is used in-depth interview to collect data. The data is analyzed when data is reached the saturation in thematic analysis. The finding is thematized and analyzed into narrative description in terms of the attitudes which includes affect (feeling), behavior (intention), and cognition (believe) towards the content in Thai digital TV.